Strategi Penggunaaan Virtual Reality dalam Simulasi Dialog Bahasaa Arab Untuk Maharah Kalam di Perguruan Tinggi - Ratna Komalasari (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2025)
The development of immersive technology such as Virtual Reality (VR) opens up new opportunities in learning foreign languages, especially in improving the maharah kalam (speaking skills) of Arabic which has been facing obstacles in terms of communicative practice and the context of language use. This study aims to analyze the strategy of using VR in Arabic dialogue simulation as an effort to improve the kalamh of university students. This study uses a qualitative approach with a descriptive-analytical study design. Data was collected through VR-based learning observations, interviews with lecturers and students, and analysis of learning documents. The results show that the use of VR through contextual dialogue simulations—such as conversations in academic, social, and Arabic cultural environments—is able to increase students' speaking boldness, fluency, pronunciation accuracy, and pragmatic understanding of Arabic. Effective learning strategies include designing real-situation-based dialogue scenarios, integrating task-based learning, and providing post-simulation reflective feedback. However, the implementation of VR still faces challenges in the form of limited infrastructure, pedagogical readiness of lecturers, and student adaptation to immersive technology. This research contributes to the development of an Arabic language learning model based on digital technology and provides strategic recommendations for strengthening the innovation of maharah kalam learning in higher education.